An appreciation of Arie de Geus' contribution to the learning organization. Issue 5 (8th June 2020) - Robinson, Graham
Abstract : Purpose: This paper aims to locate its appreciation of the life and work of Arie de Geus within the context of developments in approaches to management practice, education and learning since the Second World War. It emphasizes the important influence of top management-led applications of social science (Beckhard) and the impact of crises upon planning and the generation of memories of the future for effective organizational learning. The paper also describes the roles of learning from experience and of reflective practice in shaping de Geus' contribution. Design/methodology/approach: The approach traces the development of de Geus' career and thinking from Shell cost accountant, to top line manager in three continents, to Head of Shell Group Planning, to prize winning author, to global adviser to the World bank, etc., and as an inspirational speaker as champion of the learning organization. Findings: The paper acknowledges Arie de Geus as coining the phrase "The Learning Organization" together with his role in the foundation and development of the Society for Organizational Learning (SOL) and as an international champion of young people's learning through the processes of the Finnish Team Academy model. Social implications: Arie de Geus was an exemplar of reflective practice and applied learning. As such, his contribution might be considered as that of a sage rather than as a guru. Originality/value: The paper endeavours to emphasize the importance of the role of both the internal and external contexts for effective organizational learning, suggesting that the contribution of Arie de Geus to the field exemplifies this importance.